2002
DOI: 10.1111/j.1540-8167.2002.tb01956.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient Selection for Biventricular Pacing

Abstract: Biventricular Pacing. Introduction: Biventricular pacing improves functional status in the majority of patients with drug-refractory heart failure, dilated cardiomyopathy, and interventricular conduction delay. The aim of this study was to analyze the baseline clinical and functional data of a cohort of patients implanted with a biventricular stimulation system in a single-center experience, to verify if the pathophysiologic characteristics of patients affect outcome, and to determine if preliminary identifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
7
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(11 citation statements)
references
References 9 publications
4
7
0
Order By: Relevance
“…These findings are concordant with the presumed mechanism of CRT benefit, since reduction in the total ventricular activation time, as measured by the QRS width, probably reflects a reduction in electrical dyssynchrony. Nevertheless, the magnitude of this shortening is generally suboptimal, ranging from 20 to 30 ms in the literature and in the present study, and, therefore, QRS almost invariably remains wide 3–7 . We found that HBP + CS and TRIPLE configurations, but not HBP alone, yielded additional shortening of 16 ms and 23 ms, respectively, which suggests a potentially better clinical outcome (Figure 2A).…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…These findings are concordant with the presumed mechanism of CRT benefit, since reduction in the total ventricular activation time, as measured by the QRS width, probably reflects a reduction in electrical dyssynchrony. Nevertheless, the magnitude of this shortening is generally suboptimal, ranging from 20 to 30 ms in the literature and in the present study, and, therefore, QRS almost invariably remains wide 3–7 . We found that HBP + CS and TRIPLE configurations, but not HBP alone, yielded additional shortening of 16 ms and 23 ms, respectively, which suggests a potentially better clinical outcome (Figure 2A).…”
Section: Discussionsupporting
confidence: 54%
“…In the PROSPECT-ECG study, 16 shortening is generally suboptimal, ranging from 20 to 30 ms in the literature and in the present study, and, therefore, QRS almost invariably remains wide. [3][4][5][6][7] We found that HBP + CS and TRIPLE configurations, but not HBP alone, yielded additional shortening of The frontal plane QRS axis has only seldom been assessed in CRT studies, mostly as a preimplantation predictor of response, and with modest and contrasting results 16,[18][19][20] ; the paced QRS axis has also been used to assess the relative contribution of RV and LV pacing at different VV intervals or pacing sites. 21,22 In general, the paced QRS axis has not reached the level of confidence required for its use in clinical practice.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Of those treated by CRT, 20–30% experience no clinical benefit 6–12 . Previous studies have attempted to predict both responders and nonresponders to CRT 6,13–16 . A lack of response has been previously reported when LV dyssynchrony is absent, 7,17,18 the pulmonary artery systolic pressure is elevated, 19 LV lead location is suboptimal, 20–22 and the etiology of the cardiomyopathy is ischemic 3 .…”
Section: Introductionmentioning
confidence: 99%